Pengaruh Akuntansi Sosial, Program CSR, dan Stakeholder Engagement terhadap Keunggulan Bersaing UMKM - Muhammad Nabil Fatwa; Muhammad Indra Wardana; Maria Yovita R. Pandin (AKUNTANSI 45, 2026)
The competitive advantage of Micro, Small, and Medium Enterprises (MSMEs) in Surabaya is examined in this study in relation to social accounting, corporate social responsibility (CSR) implementation, and stakeholder involvement. Using a quantitative causal-associative approach, the research involved 60 MSME owners who actively implemented social initiatives and maintained ongoing stakeholder engagement. Questionnaires were used to gather data, which were then analyzed using SPSS version 16 with multiple linear regression and validity, reliability, t-test, and F-test analyses. The results demonstrate that the competitive advantage of MSMEs is positively and significantly impacted by social accounting, CSR practices, and stakeholder participation, both separately and together. With a coefficient of determination (R2) of 0.450, these variables account for 45% of competitive advantage, with additional factors like marketing and innovation influencing the remaining variation. Overall, the results highlight that consistent social accounting, sustainable CSR, and active stakeholder engagement enhance reputation, build trust, and strengthen MSMEs’ competitiveness in a dynamic business environment.